Prevalence of domestic violence among health center users: a retrospective longitudinal analysis - Fernandez-Mamani, Marjorie Cristel (2024)
Introduction: To determine the prevalence of domestic violence among users of a health center through a retrospective longitudinal analysis by age groups and gender. Methods: This is a retrospective longitudinal study based on data obtained from a health center in Pichari, Cusco, Peru. The sample obtained was 13,040 users of the Comprehensive Health Insurance (SIS) by non-probabilistic sampling. The evaluation was carried out using the Domestic Violence Screening Form (VIF) of the Ministry of Health (MINSA). Results: We found that children and older people have higher survival rates regarding domestic violence, the cumulative risk of domestic violence over time at different stages of development is highest in adolescence, followed by the young stage. Likewise, the cumulative risk is consistently higher for the female gender. Conclusions: Domestic violence presents a higher risk in adolescents, young people, and women. These findings highlight the urgent need to implement concrete measures to address this problem, such as prevention programs, mental health education, and strengthening support and care services for victims and their families.